1991
DOI: 10.1159/000147195
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure of Morphologically Well-Defined Type II Neurons in the Enteric Nervous System of the Porcine Small Intestine Revealed by Immunoreactivity for Calcitonin Gene-Related Peptide

Abstract: Calcitonin gene-related peptide (CGRP)-containing perikarya and axonal processes were localized by preembedding electron-microscopic immunocytochemistry in the porcine small intestine. Immunoreactive well-defined type II neurons were localized in the plexus myentericus, and plexus submucosus externus and internus. In some cases, they were found in direct contact to the basal lamina surrounding the ganlion, thus being in close apposition to the interstitial space. The perikarya are generally larger than the imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Work on human small intestine (Timmermans et al 1992) has indicated that CGRP immunoreactivity is mainly found in a neuronal population morphologically similar to the CGRP-immunoreactive (IR) somata observed in the porcine small intestine (Scheuermann et al 1987(Scheuermann et al , 1991 and mouse colon (Furness et al 2004b), i.e. in Dogiel type II neurons.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Work on human small intestine (Timmermans et al 1992) has indicated that CGRP immunoreactivity is mainly found in a neuronal population morphologically similar to the CGRP-immunoreactive (IR) somata observed in the porcine small intestine (Scheuermann et al 1987(Scheuermann et al , 1991 and mouse colon (Furness et al 2004b), i.e. in Dogiel type II neurons.…”
Section: Introductionmentioning
confidence: 92%
“…IPANs, identified by their morphology and projections in the mouse colon, are also CGRP-IR (Furness et al 2004b). Furthermore, Dogiel type II neurons, presumed to be IPANs, are CGRP-IR in the pig small intestine (Scheuermann et al 1991) and a proportion are CGRP-IR in human (Timmermans et al 1992;Brehmer et al 2004). Thus, by analogy with other species, we deduce that the CGRP-IR Dogiel type II neurons in sheep are IPANs.…”
Section: Intrinsic Cgrp-ir Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…ness 1988; Scheuermann et al 1991). These neurons are cholinergic in the guinea-pig (Li and Furness 1998) and, throughout all species investigated, non-nitrergic (Costa et al 1992bWard et al 1992;Aimi et al 1993;Furness et al 1994;Timmermans et al 1994 a, b;Brehmer and Stach 1997).…”
Section: Neuron Typesmentioning
confidence: 98%
“…Although direct functional evidence is still lacking, type II neurons have been suggested to represent the IPANs in the pig (Cornelissen et al, 1999(Cornelissen et al, , 2000(Cornelissen et al, , 2001Hens et al, 2000). For 20 years, calcitonin gene-related peptide (CGRP) has been used as a marker for type II neurons in the pig ENS (Scheuermann et al, 1987(Scheuermann et al, , 1991Hens et al, 2000). However, several studies revealed that this peptide, in colocalization with a marker for cholinergic neurons (choline acetyl transferase, ChAT), is present also in neurofilament (NF) reactive, non-type II neurons, indicating that the chemical code NF/CGRP/ChAT, with NF as structural marker, is not specific for type II neurons (Brehmer et al, 2002a,b;Jungbauer et al, 2006).…”
mentioning
confidence: 99%